Efektivitas Pelaksanaan Program Keselamatan dan Kesehatan Kerja Terhadap Terjadinya Kecelakaan Kerja di Kebun Rambutan PTPN III - Widjajanto, Adi Widjajanto (Perkumpulan Dosen Muda (PDM) Bengkulu, 2022)
The Occupational Safety and Health Management System is part of the overall company management system in order to control risks related to work activities that aim to create a safe, effective and productive workplace to prevent workplace accidents. The implementation of Occupational Safety and Health Management System which is well implemented will affect the reduction in the number of work accidents, but in some companies in Indonesia work accidents still occur even though the company has implemented Occupational Safety and Health Management System, as well as with Rambutan gardens during the application of Occupational Safety and Health Management System also still accidents, in 2016 there were 23 cases of work accidents , in 2017 there were 19 cases of work accidents, and in 2018 there were 11 cases of work accidents. The last 3 years data shows that the graph of work accidents is decreasing so that the application of the Occupational Safety and Health Management System program in Rambutan garden plantation has been implemented quite effectively although it has not been implemented optimally as a whole. The purpose of this study was to determine how the application of Occupational Safety and Health Management System and its implications for workplace accidents. The results of this study indicate that the obstacles in the implementation of Occupational Safety and Health Management System so that it has implications for workplace accidents is the application of Occupational Safety and Health Management System that has not been well implemented by management in terms of implementing OHS programs that are not on target, lack of supervision by management and lack of employee attention to the use of tools Personal Protective Equipment (PPE) and work not in accordance with the SOP.